Compliance of LC procedures by Bangladesh Bank regulation: a study on Southeast Bank Limited - Meem, Mir Tasnuva Reza (BRAC University, 2017)
This internship report is submitted in a partial fulfilment of the requirements for the degree of Bachelor of Business Administration, 2016.